The influence of cognitive schemas on the mixed anxiety-depressive symptoms of breast cancer patients - Ana Cristina Bredicean; Zorin Crăiniceanu; Cristina Oprean; Ioana Alexandra Riviș; Ion Papavă; Ica Secoșan; Mirela Frandeș; Cătălina Giurgi-Oncu; Daciana Grujic (BMC, 2020)
Abstract Background The surgical treatment of breast cancer involves various psychological consequences, which differ according to individual characteristics. Our study aimed to identify the role that cognitive schemas had in triggering anxiety and depressive symptoms in patients diagnosed with breast cancer that underwent oncological and plastic surgery treatment. Methods 64 female patients, diagnosed with breast cancer from an Oncology and Plastic Surgery Hospital, were selected to participate in this study between March-June 2018. They were divided into two groups: I. 28 patients who underwent mastectomy surgery; II. 36 patients, who required mastectomy and, subsequently, also chose to undergo breast reconstruction surgery. For the purposes of evaluating a possible change in mental health status, we employed two assessment scales: the Young Cognitive Schema Questionnaire - Short Form 3 (YSQ-S3) and the Romanian version of the Depression Anxiety Stress Scale - 21 (DASS-21R). Results Participants who underwent mastectomy and subsequent breast reconstruction surgery employed cognitive schemas that did not generate symptoms of depression or anxiety. In contrast, the cognitive schemas found in women who refused reconstructive breast surgery were significantly correlated with the presence of anxiety-depressive symptoms. The cognitive schema domain of 'disconnection and rejection' correlated uncertainly with the presence of anxiety-depressive symptoms for the group with breast reconstruction (Spearman's ρ = 0.091, p = 0.644), while for the other group the correlation was moderate-strong (Spearman's ρ = 0.647, p <  0.01). Negative emotional schemas were significantly correlated with the presence of anxiety-depressive symptoms (Spearman's ρ = 0.598, p <  0.01) in the group of participants without reconstructive surgery. Conclusion A correct identification of dysfunctional cognitive schemas and coping mechanisms at the commencement of the combined treatment in breast cancer patients could serve as an indicator for the evolution of their mental health, therefore assisting professionals in establishing the most suitable psychological, psychotherapeutic and psychiatric intervention plan.